Emerging Role of Caveolin-1 in GLP-1 Action - Puddu, Alessandra; Maggi, Davide (Frontiers in Endocrinology, 2021)
Glucagon-like peptide-1 (GLP-1) is a gut hormone mainly produced in the intestinal epithelial endocrine L cells, involved in maintaining glucose homeostasis. The use of GLP-1 analogous and dipeptidyl peptidase-IV (DPP-IV) inhibitors is well-established in Type 2 Diabetes. The efficacy of these therapies is related to the activation of GLP-1 receptor (GLP-1R), which is widely expressed in several tissues. Therefore, GLP-1 is of great clinical interest not only for its actions at the level of the beta cells, but also for the extra-pancreatic effects. Activation of GLP-1R results in intracellular signaling that is regulated by availability of downstream molecules and receptor internalization. It has been shown that GLP-1R co-localizes with caveolin-1, the main component of caveolae, small invagination of the plasma membrane, which are involved in controlling receptor activity by assembling signaling complexes and regulating receptor trafficking. The aim of this review is to outline the important role of caveolin-1 in mediating biological effects of GLP-1 and its analogous.